Development of a conceptual framework of sexual health for married elderly women: An exploratory mixed method study - Farzaneh Saadatmand; Mitra Savabi-Esfahani; Zahra Heidari; Marjan Beigi (PLoS ONE, 2025)
Background Identifying elderly women’s sexual health demands based on their lived experience is essential since it leads to their sexual rights promotion. The present framework was designed to identify sexual demands, develop a reliable and valid questionnaire, and present it to policymakers. Methods This conceptual framework was designed in four phases using an exploratory sequential approach. The first phase included a review of related literature to identify elderly women’s sexual health demands. In the second phase, the qualitative phase, the participants will be interviewed to identify their sexual health demands. Data will be collected through in-depth semi-structured interviews until data saturation. In the third phase, a draft questionnaire will be provided using the data from the qualitative study and literature review to measure the sexual health demands of elderly women. Afterward, the face and content validity, as well as the construct and criterion validity, will be determined. The construct and criterion validity will be assessed using exploratory factor analysis and a cross-sectional study on elderly women, respectively. Finally, the reliability of the questionnaire will be determined. In the fourth phase, using the classical Delphi technique, the panel of experts will select the most important demands to present to policymakers. Results Based on a literature review conducted from October 20, 2023, to March 15, 2024, the demands were categorized into three main groups: “the elimination of ageist attitudes,” “the elimination of sexism,” and “the elimination of sexual retirement.” Other data and their integration with the literature review data to finalize the categories will be obtained after conducting qualitative interviews. Afterward, the questionnaire will be developed and psychometrically evaluated. Finally, the demands will be prioritized for policymakers. Conclusion According to the results, elderly women face social and cultural challenges in maintaining sexual health. Based on the presented methods, comprehensive and complete identification of demands in different cultures can facilitate sexual health planning.